2010
DOI: 10.1021/ol102294g
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Michael Addition of Nitroalkanes to Chalcones Using Chiral Squaramides as Hydrogen Bonding Organocatalysts

Abstract: A series of squaramide-based organocatalysts were facilely synthesized and applied as hydrogen bonding organocatalysts in the enantioselective Michael addition of nitroalkanes to chalcones. These organocatalysts promoted the Michael addition with low catalyst loading under high temperature (80 °C), affording the desired R or S enantiomers of the products flexibly in high yields with excellent enantioselectivities (93-96% ee) by the appropriate choice of organocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(161 citation statements)
references
References 41 publications
4
156
0
1
Order By: Relevance
“…The enantioselectivity was determined by HPLC analysis (77% ee, Daicel CHIRALPAK AD-H, 5% isopropanol/hexane, 1.0 mL/min, 229 nm; t r (major enantiomer) = 18. Spectroscopic data of γ-nitroketones 4 are in agreement with published data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. …”
Section: Typical Procedures For the Michael Addition Of Nitroalkanes Tsupporting
confidence: 84%
See 1 more Smart Citation
“…The enantioselectivity was determined by HPLC analysis (77% ee, Daicel CHIRALPAK AD-H, 5% isopropanol/hexane, 1.0 mL/min, 229 nm; t r (major enantiomer) = 18. Spectroscopic data of γ-nitroketones 4 are in agreement with published data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. …”
Section: Typical Procedures For the Michael Addition Of Nitroalkanes Tsupporting
confidence: 84%
“…As pioneering works in organocatalytic asymmetric Michael addition of carbon nucleophiles to α,β-unsaturated carbonyl compounds, Yamaguchi's group reported that Michael addition of malonates to enones could be catalyzed by a proline alkali metal salt [6][7][8][9][10][11][12]. They later succeeded in the asymmetric Michael addition of nitroalkanes to enones using a proline rubidium salt-catalyst [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. We recently reported that an O-silylated L-serine lithium salt was an effective catalyst for asymmetric Michael addition of malonates to enones to give various 1,5-ketoesters in good yields with high enantioselectivity [33].…”
Section: Introductionmentioning
confidence: 99%
“…The chalcone molecule might act as a Michael acceptor, and establish a covalent bond [3,35]. The p bonds can be electron donors in the formation of a charge-transfer complex (ionic bond).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, hoy en día una serie de catalizadores a base de escuaramida se han desarrollado y aplicado con éxito en varias reacciones asimétricas (Malerich et al, 2008;Qian et al, 2010;Yang y Du, 2010) como: la reacción de Friedel-Crafts (Qian et al, 2010); la α-aminación de compuestos 1.3-dicarbonílicos con nitroalquenos (Konishi, Lam, Malerich y Rawal, 2010) y la adición de Michael enantioselectiva (Malerich et al, 2008;Xu et al, 2010;Zhu et al, 2010).…”
Section: Las Escuaramidas Como Organocatalizadoresunclassified